Lettering, Kaisar-i-Hind Building - Ghosh, Ayan (2023)
Lettering at the Kaisar-i-Hind building that houses the Enforcement Directorate. The ornamental pilasters on either side are of the Tuscan order (the plain shaft that rests on an unadorned base and has a simple capital). The metal grille on the lintel has a swastika on a circular base. Similar swastikas also appear on the windows of the building.